Succession Planning in Australian Farming - John Hicks; Richard Sappey; Parikshit Basu; Deirdre Keogh; Rakesh Gupta (Australasian Accounting, Business and Finance Journal, 2012)
The theme of this paper is that succession planning in Australian farming is under-developed. It may be linked to economic and social change which suggests that farmers need to adapt to generational change but this is being resisted or ignored. The implications of this are the slow decline of family farming, a poor transfer of skills and knowledge to subsequent generations of farmers in some parts of the agricultural sector and the potential for an extension of the financial services industry to develop a more effective raft of succession planning measures to mitigate the effects of a traditional approach to succession in agriculture.
Keywords: Succession planning; farming; Australia; food security